2016
DOI: 10.1007/s10719-016-9716-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an amino acid residue critical for the specificity and activity of human Gb3/CD77 synthase

Abstract: Human Gb3/CD77 synthase (α1,4-galactosyltransferase) is the only known glycosyltransferase that changes acceptor specificity because of a point mutation. The enzyme, encoded by A4GALT locus, is responsible for biosynthesis of Gal(α1–4)Gal moiety in Gb3 (CD77, Pk antigen) and P1 glycosphingolipids. We showed before that a single nucleotide substitution c.631C > G in the open reading frame of A4GALT, resulting in replacement of glutamine with glutamic acid at position 211 (substitution p. Q211E), broadens the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…S2 ). Interestingly, α1-4 GALT, also known as Gb3 synthase, is the only known GT enzyme that changes acceptor specificity because of point mutations, and therefore is considered to be a highly promiscuous enzyme 31 , 32 . In addition, a β1-4 GALT gene from Neisseria meningitidis , pglA , catalyses both β1-4 and α1-3 linkages between the galactose and deoxyhexose in a trisaccharide structure 14 .…”
Section: Resultsmentioning
confidence: 99%
“…S2 ). Interestingly, α1-4 GALT, also known as Gb3 synthase, is the only known GT enzyme that changes acceptor specificity because of point mutations, and therefore is considered to be a highly promiscuous enzyme 31 , 32 . In addition, a β1-4 GALT gene from Neisseria meningitidis , pglA , catalyses both β1-4 and α1-3 linkages between the galactose and deoxyhexose in a trisaccharide structure 14 .…”
Section: Resultsmentioning
confidence: 99%
“…We also attempted to evaluate the effect of NOR mutation (c.631C>G) on activity of the Gb3/CD77 synthase in vivo and how it relates to our earlier studies ex vivo and in vitro [ 5 7 ]. In our study on a transfected cell line[ 7 ], activity of the consensus Gb3/CD77 synthase was higher than activity of the p.Q211E mutein, in contrast to our results with the purified recombinant variants of the enzyme. The results of this study suggest that the p.Q211E enzyme’s superpromiscuity comes at the cost of P1 synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, c.631C>G mutation in A4GALT , leading to p.Q211E substitution in Gb3/CD77 synthase (rs397514502), alters the enzyme specificity, rendering it able to synthesise all the three P1PK system antigens: P k , P1 and NOR[ 6 ]. This makes Gb3/CD77 synthase a unique case of a promiscuous glycosyltransferase, radically unmoored from the old ‘one enzyme-one linkage’ tenet[ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…P k and P1 are both expressed on the surface of human red blood cells. Recently, it has been shown that the p.Q211E variant of A4GALT is also able to synthesize NOR antigens, which are rare glycosphingolipids with a terminal Gal(α1–4)GalNAc moiety present in erythrocytes of patients with NOR polyagglutination syndrome [ 135 , 136 ] ( Figure 6 A). Importantly, the existence of some individuals with a genetic deficiency in A4GALT without obvious clinical consequences suggests that selective inhibition of this enzyme could be well tolerated by FD patients [ 137 , 138 ].…”
Section: A4galt: Reaction Mechanism and Enzymatic Productsmentioning
confidence: 99%